The district hospital: A rare story of success and a way forward - Jason Fader; Tim Fader (African Journal of Primary Health Care & Family Medicine)
The district hospital is a vital part of the healthcare system in sub-Saharan Africa. It is the key to enabling Primary Health Care to be done well, which in turn can allow for Universal Health Coverage to be achieved. There are numerous challenges at district hospitals making successful ones somewhat rare. One example of a successful district hospital is put forth in this article. In order to increase the number of successful district hospitals a means of sharing solutions to common problems needs to be created, which would ideally be an online repository of said solutions, available to any interested district hospital.